Mechanical Strength Analysis of Composites As Advanced And Sustainable Future Materials - Wahyu Fajar Manzilah; Dr. Ikhwanul Qiram, S.T., M.T. (Fakultas Teknik Universitas PGRI Banyuwangi, 2025)
The development of composite materials has become one of the efforts to improve energy efficiency, driven by increasing environmental concerns and the depletion of fossil and mineral resources. These issues have encouraged researchers across various countries to seek accurate and effective solutions, particularly in reducing the use of metallic materials in a sustainable manner. Research on natural fiber composites presents significant potential as an alternative sustainable material; however, technical challenges, economic value, and real-world application must be overcome in order to compete with conventional materials. Efforts to develop more environmentally friendly fiber processing methods are essential to maintain environmental stability during production and usage. Improving mechanical properties through variations and combinations of fibers and matrices tailored to specific functions or mechanical needs is also critical. Based on the research and analyses conducted, composite materials demonstrate good durability and mechanical strength using various components such as carbon or aramid fibers, combined with different types of matrices like polyester resin, epoxy, binders, and polypropylene. Each type of matrix significantly influences the resulting mechanical strength. With the continuous advancement of research, natural fibers offer great potential due to their abundant availability and eco-friendliness compared to carbon or aramid fibers, even though their mechanical strength is not yet on par